Can we drink the ocean? : a book about water - Gidget Jimenez-Roceles; Isabel Roxas, illustrator (uezon City : Adarna House, Inc., 2008)
Discover the properties of water, water cycle, water treatment and distribution, and water conservation.
Keywords: Childre's stories